A Participatory Evaluation of Transforming First Year LLB Into Block Mode - Gayani Samarawickrema; Tristan Galloway; Kathleen Raponi; Gerard Everett (Legal Education Review)
This paper adopts a participatory evaluation approach to identify successes and challenges experienced by a group of academics in redesigning and delivering the first year of the Law degree (LLB) in block mode in an Australian university. This transformation into an intensive four-week block necessitated an overhaul of curricula, assessment regimes, teaching practices and delivery processes. The evaluation of the academics staff experience focused on five themes: (1) course design and development, (2) satisfying learning outcomes and accreditation standards, (3) implementing student engagement strategies, (4) embedding block mode principles, and (5) establishing effective assessment regimes. For each theme, participants identified the successes, challenges, and lessons learned. The study highlighted the value of early design-specialist involvement and collaboration in course design including the importance of being aware of the legal accreditation body requirements. The criticality of focused active learning and the need to balance lecture-style delivery with knowledge-consolidating practical legal analysis exercises was emphasised. Also stressed was wellbeing, including sensitivity to individual student circumstances and strategies that successfully manage staff and student workloads alongside academic integrity. Unintended benefits such as professional learning through the collaboration, refining personal thinking related to pedagogy in the block were consequences of this evaluative approach.